1992
DOI: 10.1111/j.1749-6632.1992.tb24599.x
|View full text |Cite
|
Sign up to set email alerts
|

B‐Cell Subsets Defined by the FcεRa

Abstract: The data summarized herein demonstrate the utility of the low-affinity Fc epsilon R in delineating murine B-cell subsets. In the peritoneal cavity, the Fc epsilon R appears to be a reliable marker in distinguishing between conventional (Fc epsilon R+) and Ly-1/sister (Fc epsilon R-) B cells. In the spleens of normal animals, flow cytometric and histologic studies established that a distinct population of Fc epsilon R- B cells is also present and comprises the marginal zones. Thus in the spleen, the Fc epsilon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Thus, the decreased levels of CD23 may be relatively specific for those B cells that are autoreactive. These data indeed correlate with reports in other lupus models (12,44,45).…”
Section: Phenotype Of B Cells In the 3h9ki Mice After Cgvh Inductionsupporting
confidence: 81%
“…Thus, the decreased levels of CD23 may be relatively specific for those B cells that are autoreactive. These data indeed correlate with reports in other lupus models (12,44,45).…”
Section: Phenotype Of B Cells In the 3h9ki Mice After Cgvh Inductionsupporting
confidence: 81%
“…To further assess the maturation status of B cells in the spleen, we looked at the expression of CD23. CD23 is a marker for resting mature B cells that are IgM lo IgD hi and thus represent cells that have undergone class switching (40,86). This analysis showed a slightly increased number of mature resting B cells in the fps Ϫ/Ϫ mice that was restored to wild-type levels in the fps Ϫ/Ϫ :Tg mice.…”
Section: Vol 22 2002 Enhanced Endotoxin Sensitivity In Fps/fes-nullmentioning
confidence: 85%
“…These cells express CD5 and IgM (12). Recently it has been suggested that TLRs play a role in signaling events in B1 B cells and T cell-independent immune responses (1).…”
Section: B Lymphocyte Activation By Human Papillomavirus-like Particlmentioning
confidence: 99%